Drug-loaded nanoparticles for intra-articular injection - Piaopiao Pan; Konstantina Simou; Yanting Ouyang; Lawrence Shere; Jon A. Preece; Simon W. Jones; Edward T. Davis; Yanling Lan; Zhenqiu Chen; Zhenyu Jason Zhang; Qingguo Li (PLoS ONE, 2026)
Drug loaded nanoparticles (NPs) were developed as a model intra-articular injection (IAI) formulation to mitigate early stage osteoarthritis (OA). Different types of celecoxib-loaded nanoparticles were prepared by a hybrid method that combines homogenization and solvent evaporation. The hydrodynamic diameter of the nanoparticles prepared were approximately 200 nm (PLLA: 238 ± 19 nm; PCL: 249 ± 28 nm; PLA: 252 ± 18 nm; PMMA: 234 ± 21), and zeta potential were about −40 mV (PLLA: −45.3 ± 2.3 mV; PCL: −38.0 ± 0.9 mV; PLA: −44.4 ± 3.2 mV; PMMA: −45.5 ± 2.7 mV). Our friction data evidences that nanoparticles could improve considerably the lubrication between a stainless steel sphere and a silicone elastomer that were used as model substrates. Quartz Crystal Microbalance (QCM) and Atomic Force Microscope (AFM) measurements were carried out to unravel the lubrication mechanism. The magnitude and amount of NPs adsorbed on the surface determines the effect of lubrication. Drug release experiment suggests that nanoparticles could release up to more than one week, when being compared with free celecoxib. NPs formulation exhibited excellent biocompatibility in cytotoxicity of chondrocytes experiment.